Hybrid Systems: Computation and Control - Egerstedt, Magnus (Springer, 2017)
This volume contains the proceedings ofthe 11th Workshop on Hybrid Systems: Computation and Control (HSCC 2008) held in St. Louis, Missouriduring April 22–24,2008.The annual workshop on hybrid systems focuses on researchin - bedded,reactivesystemsinvolvingtheinterplaybetweensymbolic/switchingand continuous dynamical behaviors. HSCC attracts academic as well as industrial researchers to exchange information on the latest developments of applications and theoretical advancements in the design, analysis, control, optimization, and implementation of hybrid systems, with particular attention to embedded and networked control systems. New for this year was that HSCC was part of the inaugural CPSWEEK (Cyber-Physical Systems Week) – a co-located cluster of three conferences: HSCC, RTAS (Real-Time and Embedded Technology and Applications Sym- sium), and IPSN (International Conference on Information Processing in Sensor Networks). The previous workshops in the series of HSCC were held in Berkeley, USA (1998),Nijmegen,TheNetherlands(1999),Pittsburgh,USA(2000),Rome,Italy (2001), Palo Alto, USA (2002), Prague, Czech Republic (2003), Philadelphia, USA (2004),Zurich, Switzerland (2005) , Santa Barbara,USA (2006), and Pisa, Italy (2007). We would like to thank the Program Committee members and the reviewers for an excellent job of evaluating the submissions and participating in the online Program Committee discussions. We are grateful to the Steering Committee for their helpful guidance and support. We would also like to thank Patrick Martin for putting together these proceedings, and Jiuguang Wang for developing and maintaining the HSCC 2008 website. January 2008 Magnus Egerstedt Bud Mishra Organization HSCC 2008 was technically co-sponsored by the IEEE Control Systems Society and organized in cooperation with ACM/SIGBED.